Traumatic Aneurysm of Axillary Artery Following DisPfacement of Shoulder - Piñeyro, Alberto; Bergalli, Luis; Fernández, Miguel (Cirugía del Uruguay, 1981)
Report of one case of traumatic aneurism of axillary artery following displacement of shoulder, treated successfully by surgery. The frequency and etiology of this condition is discussed in the paper.